ANALISIS YURIDIS PERBANDINGAN SISTEM PROPORSIONAL TERTUTUP DAN PROPORSIONAL TERBUKA DALAM PEMILU LEGISLATIF - Infanteri, Wonder Infanteri; Poltak Siringoringo; Tomson Situmeang (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
This study compares Indonesia’s parliamentary elections using open and closed proportional voting methods. Closed proportional systems only let voters choose political parties, not specific individuals; open proportional systems let voters choose individual candidates from party lists. The aim of this analysis is to assess the strengths and weaknesses of each system in terms of democracy, representation, and government effectiveness. The research finds that the open-list proportional system offers benefits in terms of individual representation and the accountability of elected officials to voters. Voters have the opportunity to select candidates they consider competent and aligned with their aspirations. However, this system also tends to increase party fragmentation and campaign costs. Conversely, the closed-list proportional system grants greater power to political parties in determining elected representatives, which can reduce individual representation but enhance party stability and campaign efficiency. In conclusion, both systems have strengths and weaknesses that need to be considered within Indonesia’s political and social context. The open-list proportional system supports voter participation and accountability of elected officials, while the closed-list proportional system favors political stability and efficiency. Choosing the ideal electoral system requires balancing individual representation and political stability in line with Indonesia’s democratic dynamics.